Conscientious objection in the Italian legal system between application difficulties and attempts at resolution (Stato, Chiese e pluralismo confessionale, 2024)
The essay examines freedom of conscience and conscientious objection within the Italian constitutional framework, with particular attention to the problematic case of interruption of pregnancy. It identifies and highlights the pros and cons of the solutions envisaged or actually adopted to date to deal with the high number of objectors registered in many Italian healthcare facilities.